Root Causes of Brake Caliper Problems as A Corrective Action in Front of LH: A Case Study in Manufacturing Industry - Aisyah, Siti; Huwae, Priskila Timaha; Debora, Fransisca; Jaqin, Choesnul; Sitorus, Tosty Maylangi (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The industrial sector is the backbone of the country in building the defense sector and economic stability that needs to maintain productivity and be competitive. One of the companies that manufacture automotive components, Mitsubishi, manufactures automotive components and must have zero defect requirements. However, in practice, it was found that 1 (one) unit of CJM had a brake caliper malfunction in the condition that the unit was ready to be sent to the carpool consumer of a company that produces automotive components. The damage is a discrepancy in the diameter of the piston seal, which closes the gap between the piston and the piston housing, allowing for brake fluid leakage, which affects the